Contextualized editorial practices: Maria Cecília de Souza Minayo and the journal Ciência & Saúde Coletiva - Hugo Spinelli; Viviana Martinovich (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
This interview forms part of a series of dialogues that Salud Colectiva has been holding with key editors in the field, with the purpose of examining the similar difficulties confronted by Latin American journals and the diverse ways the journals have faced these difficulties as a likely starting point for uncovering contextualized solutions. In this interview, carried out in 2015 in the Instituto de Salud Colectiva of the Universidad Nacional de Lanús, Maria Cecília de Souza Minayo speaks to us about the context in which the journal Ciência & Saúde Coletiva emerged, the political disputes existing within the collective health field, and the relevance of debate as a constitutive process of science itself. Additionally, Minayo analyzes both the importance of funding to the growth of a journal and the problems and difficulties in obtaining funds, which puts into evidence the lack of policy regarding scientific publishing in Brazil.